2009
DOI: 10.1111/j.1600-0501.2008.01694.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability change of chemically modified sandblasted/acid‐etched titanium palatal implants. A randomized‐controlled clinical trial

Abstract: Aim: The aim of this randomized‐controlled clinical study was to examine stability changes of palatal implants with chemically modified sandblasted/acid‐etched (modSLA) titanium surface compared with a standard SLA surface, during the early stages of bone healing. Materials and methods: Forty adult volunteers were recruited and randomly assigned to the test group (modSLA surface) and to the control group (SLA surface). The test and control implants had the same microscopic and macroscopic topography, but dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 25 publications
5
26
1
1
Order By: Relevance
“…29 The current results show only slight changes of stability during the first 2 weeks followed by the typical decrease of stability from week 2 to week 4. The same was found by Schä tzle et al, 30 who investigated the healing period of palatal implants with SLA surface and 4.1-mm diameters inserted in the midpalatal region. They investigated a subsequent increase of ISQ values.…”
Section: Discussionsupporting
confidence: 59%
“…29 The current results show only slight changes of stability during the first 2 weeks followed by the typical decrease of stability from week 2 to week 4. The same was found by Schä tzle et al, 30 who investigated the healing period of palatal implants with SLA surface and 4.1-mm diameters inserted in the midpalatal region. They investigated a subsequent increase of ISQ values.…”
Section: Discussionsupporting
confidence: 59%
“…For implants placed in the maxilla, only palatal-inserted orthodontic implants (Orthosystem ® , Institut Straumann AG, Basel, Switzerland) with a modSLA surface showed signifi cantly increased ISQ values after 12 weeks of healing compared to SLA implants (electronic RFA). Furthermore, it was reported that the transition point from decreasing to increasing ISQ values was obtained after 28 days for modSLA and after 35 days for SLA [ 172 ] supporting the study by Oates et al [ 168 ]. These results, taken together, suggest that modSLA implants integrate faster compared to SLA implants in the early healing period, when investigating implant stability.…”
Section: Modsla: On Cp Ti Tissue-level Implantssupporting
confidence: 60%
“…Modifications of dental implants, leading to increased surface energy, have shown a larger increase in ISQ from insertion to 12 weeks than controls in a randomized trial. [10] However, the treatment effect in that trial appeared less than the effect observed in the present trial, suggesting that the use of local drug release might be a more promising principle than physicochemical surface modifications.…”
Section: Discussioncontrasting
confidence: 47%